2015
DOI: 10.1016/j.thromres.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the platelet count in patients with chronic hepatitis C

Abstract: Background There are many potential causes of thrombocytopenia in patients with chronic hepatitis C (CHC). Aims We sought to determine the association between thrombopoietin (TPO) level, immature platelet fraction (IPF), immunoglobulin G (IgG) level, spleen size, and the platelet count in CHC. Methods We studied a consecutive sample of patients enrolled in an observational study at a referral-based research center, excluding subjects based on eligibility criteria. TPO, glycocalicin, and von Willebrand Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Moreover, there was a highly significant inverse correlation between RP% and platelet count (r = -0.698; P < 0.001). The same association was found between IPF% and platelet count in prior studies reported by Zucker et al [30] and Tana et al [31] , this suggested that peripheral platelet destruction was the main cause of thrombocytopenia in chronic hepatitis C patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, there was a highly significant inverse correlation between RP% and platelet count (r = -0.698; P < 0.001). The same association was found between IPF% and platelet count in prior studies reported by Zucker et al [30] and Tana et al [31] , this suggested that peripheral platelet destruction was the main cause of thrombocytopenia in chronic hepatitis C patients.…”
Section: Discussionsupporting
confidence: 81%
“…Hypersplenism is often implicated in thrombocytopenia in the portal hypertensive or cirrhotic patient. Another possible mechanism of splenic consumption of platelets occurs when platelets are opsonized by immunoglobulin and sequestered in the spleen [31] . Splenomegaly was significantly more common in thrombocytopenic patients than in those with normal platelet counts (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…With the evolvement of liver tissue fibrosis, thrombopoietin levels decrease, while PLT production is reduced (24,25). It is well known that the liver is the only human organ that synthesizes ALB.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of declining platelet counts, while not previously described in CFLD, is an important finding that has been described in various liver diseases ranging from cirrhosis‐related liver diseases to noncirrhotic portal hypertension. In chronic hepatitis C, platelets have been described to decline with advancing disease even prior to reaching cirrhosis with improvement after sustained viral eradication even at stages prior to cirrhosis . In noncirrhotic portal hypertension, the declining platelet counts over time was associated with mortality .…”
Section: Discussionmentioning
confidence: 99%